Answer:
9c
Step-by-step explanation:
if you take 8c and add another c, it equals 9c
Answer:
The extraneous solution is 4.
Step-by-step explanation:
First, let us calculate the value of 'x' without squaring both side of the expression. This is illustrated below:
-5 = 3x - 7
Collect like terms
-5 + 7 = 3x
2 = 3x
Divide both side by 3
x = 2/3.
Now, let us calculate the value of 'x' by squaring both side of the expression. This is illustrated below:
(-5)^2 = (3x - 7)^2
25 = (3x - 7)(3x - 7)
25 = 9x^2 - 21x - 21x + 49
9x^2 - 42x + 49 - 25 = 0
9x^2 - 42x + 24 = 0
Solving by factorisation:
Multiply the first term i.e 9x^2 and 3rd term i.e 24 together. The result is 216x^2.
Next, we shall obtain two factors of 216x^2 such that when we add them together, it will give the 2nd term i.e -42x in the equation. These factors are: -6x and -36x
Now we can write the above equation as:
9x^2 - 42x + 24 = 0
9x^2 - 6x - 36x + 24 = 0
3x(3x - 2) - 12(3x - 2) = 0
(3x - 12)(3x - 2) = 0
3x - 12 = 0 or 3x - 2 = 0
3x = 12 or 3x = 2
x = 12/3 or x = 2/3
x = 4 or 2/3.
We can see that when we solve the question without squaring both side, the value of x is 2/3. But when we solve by squaring both side, the value of x are 4 and 2/3.
Therefore, the extraneous solution to the question is 4.
Answer:
TU = 12
Step-by-step explanation:
Given
TU = x − 1
SU = 3x − 7
ST = x + 7
TU = ?
Then we can say that
SU = ST + TU
⇒ 3x − 7 = (x + 7) + (x − 1)
⇒ 3x − 7 = 2x + 6
⇒ x = 13
Finally, we get
TU = x − 1
⇒ TU = 13 - 1
⇒ TU = 12
Therefore,
ST = x + 7 = 13 + 7 = 20
SU = 3x − 7 = 3*(13) - 7 = 32
Answer:
I think it's 8 because the other sides are equal, so x and 8 should be equal as well